2017
DOI: 10.1016/j.jpeds.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Using Eye Movements to Assess Language Comprehension in Toddlers Born Preterm and Full Term

Abstract: Objective To assess language skills in preterm and full term children using a standardized language test and eye-tracking methods. Study design Children born ≤32 weeks gestation (n = 44) were matched on sex and socioeconomic status to full term children (n = 44) and studied longitudinally. The Bayley Scales of Infant and Toddler Development- Third Edition (BSID-III) were administered at 18-months (corrected for prematurity as applicable). The Looking-While-Listening (LWL) task simultaneously presents two pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…We further found weak associations with later vocabulary and school readiness measures. Unlike Loi, Marchman, Fernald, & Feldman (2017), who examined lexical processing in 18-month-olds born pre-term, we did not find that lexical processing was predictive of outcomes when concurrent vocabulary was also included in the model. We suggest that this is because by 36 months of age, lexical processing abilities have largely played their role in helping children to learn new word meanings and no longer have as strong a predictive ability.…”
Section: Discussioncontrasting
confidence: 99%
“…We further found weak associations with later vocabulary and school readiness measures. Unlike Loi, Marchman, Fernald, & Feldman (2017), who examined lexical processing in 18-month-olds born pre-term, we did not find that lexical processing was predictive of outcomes when concurrent vocabulary was also included in the model. We suggest that this is because by 36 months of age, lexical processing abilities have largely played their role in helping children to learn new word meanings and no longer have as strong a predictive ability.…”
Section: Discussioncontrasting
confidence: 99%
“…Why are some children faster in processing spoken language than others? Variation in real‐time language processing skill is likely to be related to individual differences in a host of neurodevelopmental factors, for example, premature birth, that shape trajectories of learning (Loi et al., 2017). This variation might also be the result of genetic factors which contribute to more efficient learning (Tucker‐Drob & Harden, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of children's accumulated vocabulary knowledge, that is, vocabulary size, are often derived from parent report checklists, such as the English‐language MacArthur‐Bates Communicative Development Inventories (Fenson et al., 2007) and its Spanish‐language adaptation (Jackson‐Maldonado et al., 2003). While parent reports of vocabulary size are widely used and predictive of later outcomes (Morgan et al., 2015), they capture estimates of the products of learning, and thereby, may only indirectly index the dynamic mechanisms involved in the process of early learning (Loi, Marchman, Fernald, & Feldman, 2017). Measures of online language comprehension, in contrast, capture children's proficiency in processing the incoming speech signal and linking speech to referents in the world around them in real time.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that reading decrements in children born preterm represented a component of global deficits. An explanation for this distinctive pattern of prediction is that reading difficulties in children born preterm represent the cumulative effect of many neuropsychological factors, including early brain abnormalities [46] and multiple neuropsychological weaknesses, such as slow speed of processing [47], weak verbal working memory [48], deficits in oral language [9,10], and decreased intelligence [16].…”
Section: Discussionmentioning
confidence: 99%